Integration along the Abuja road map - A progress report - Jaime de Melo; Meriem Nouar; Jean-Marc Solleder (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
This paper reviews integration among the eight African Regional Economic Communities by comparing their characteristics and progress with three other South–South Regional Integration Arrangements. Three conclusions emerge: (i) slow progress towards meeting overly ambitious objectives; (ii) small changes in the destination of trade across all Regional Economic Communities, indicative of persistent high trade costs and few new manufactures products destined for geographically close markets; and (iii) compared with other South–South Regional Integration Arrangements, the Regional Economic Communities include a high number of provisions not covered in Word Trade Organization negotiations, but these have low legal enforceability. Reasons for this slow progress are explored in the paper.
Keywords: F13; F55; F63; 330; intégration régionale